Penyusunan Bibliografi Beranotasi tentang Tan Malaka di UPT Perpustakaan Proklamator Bung Hatta - Nofrianda, Nofrianda; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
Abstract The writing of this paper aims to describe how the needs of visitors about the Tan Malaka collection, describe the process of making annotated Tan Malaka bibliography and describe the constraints and efforts in establishing the Tan Malaka annotated bibliography at the UPT Library of Bung Hatta Proklamator. This type of research is descriptive in that it explains the making of annotated bibliography about Tan Malaka at the Bung Hatta Library UPT. Data collection techniques through direct observation to the location and interviews and data collection by reading and studying sources in the form of books, literature, and teaching materials. Based on the data processed can be concluded as follows. First, the information needs of users about annotated bibliography about Tan Malaka, namely: education, reference materials and research. Second, making annotated bibliography about Tan Malaka has several stages, namely: (a) determining the title of the bibliography, because the availability of books is quite a lot and is a book that is in great demand; (b) collection of library materials or information retrieval, a book about Tan Malaka in the Bung Hatta Library UPT 34 titles; (c) selection of library materials, by checking one by one the Tan Malaka book collection; (d) classification or classification, carried out by using numerical notation sequence numbers; (e) creation of keywords, based on the book's title and the annotation of Tan Malaka's book; (f) index preparation, Tan Malaka's annotated biblographic index consists of author index, keywords and titles arranged in alphabetical order; (g) typing the text, using Times New Roman writing style, font size 12, and space 1; (h) examination of the final bibliographic manuscript. Third, the constraints and efforts in making annotated bibliography about Tan Malaka, namely: (a) the preparation of Tan Malaka's collection of books is irregular and the efforts made are doing stock taking; (b) the collection of Tan Malaka only has 1 copy and the effort to do is take action over the media.Keywords: annotated bibliography; Tan Malaka.